2011
DOI: 10.1088/0029-5515/51/12/123008
|View full text |Cite
|
Sign up to set email alerts
|

IFMIF/EVEDA lithium test loop: design and fabrication technology of target assembly as a key component

Abstract: The engineering validation and engineering design activity (EVEDA) for the International Fusion Materials Irradiation Facility (IFMIF) is proceeding as one of the ITER broader approach activities. In the concept of the IFMIF, two 40 MeV deuteron beams are injected into a liquid Li stream (Li target) flowing at a velocity of 15 m s −1. The EVEDA Li test loop (ELTL) is aimed at validating the hydraulic stability of the Li target at a velocity up to 20 m s −1 under a vacuum condition of 10 −3 Pa as the most impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…On the other hand, the solubility of nitrogen and hydrogen in lithium is large even at around the melting point of lithium; therefore, both elements should be removed from the liquid lithium chemically with other traps, which are so called hot traps. The related recent activities of lithium purification studies were reported in the references [8][9][10][11][12][13][14][15][16][17][18], and the content of the lithium test facility of IFMIF have been reported in the references [8,9,[19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the solubility of nitrogen and hydrogen in lithium is large even at around the melting point of lithium; therefore, both elements should be removed from the liquid lithium chemically with other traps, which are so called hot traps. The related recent activities of lithium purification studies were reported in the references [8][9][10][11][12][13][14][15][16][17][18], and the content of the lithium test facility of IFMIF have been reported in the references [8,9,[19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…As a major Japanese activity for the Lithium Target Facility of the IFMIF, we designed and constructed the EVEDA lithium test loop, which is the largest liquid lithium test loop in the world, and started validating it in 2012 [3,4]. Along with the validation, we have been developing the technology for the safe handling of lithium since 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Quest for more intense neutron source resulted in a combination of Li target and intense deutron or proton beams to avoid destruction of target itself by own generated neutrons. The facility of the internaitional fusion material irradiation facility (IFMIF) is now under development to generate 10 16-17 neutrons per second at 14MeV comtinuously [1,2]. In the early phase of the development, the solid target was abandoned, since the solid target sufferes strongest irradiation damage from own neutrons, and results in destruction before full irradiation on the test specimen is completed.…”
Section: Introductionmentioning
confidence: 99%